Wind Turbine Power Curve Update Based on Atmospheric Conditions and Structural Fatigue - Bingöl, Ferhat; Demir, Erdem; Gökçen Akkurt, Gülden (Izmir Institute of Technology, 2020)
Wind energy is still developing industry and people who work in this industry working hard to accomplish the difficulties. Problems are not arise only by nature of wind but technological developments, methods and even market pressure itself. Wind turbine theoretical power curves are given only for certain conditions and one can easily say that those conditions are not met in real sites. This difference generates a uncertainty in AEP calculations thus financial models become less reliable. Shifting power curve by taking atmospheric effects into account will give more realistic power curve thus more accurate AEP and financial models. In this study, effects of atmospheric conditions and correction methods on NREL 5MW wind turbines power curve have been investigated and importance of corrected power curve has been discussed.

Rüzgar enerjisi hala gelişmekte olan bir endüstridir ve bu alanda çalışan insanlar ortaya çıkan zorlukları çözmek için ciddi çalışma içerisindedir. Ortaya çıkan problemler sadece doğanın ortayta çıkardığı problemler değil, teknolojik gelişmeler, kullanılan metodlar ve hatta pazarın yarattığı ticari baskıdan dolayı ortaya çıkmaktadır. Rüzgar türbinlerinin teorik olarak veirlen güç eğrileri belirli koşullar için hesaplanmakta ve hemen hiç bir gerçek sahada bu koşullar elde edilememektedir. Ortaya çıkan bu fark ise yıllık enerji üretimi hesaplarında bize bir belirsizlik getirmektedir bundan dolayı yapılan finansal modellerde güvenilirliğini yitirmektedir. Atmosferik etkileri göz önüne alarak güç eğrisinin güncellenmesi, daha gerçekci bir güç eğrisi elde edilmesine ve daha doğru ve güvenilir yıllık üretim hesabı ve finansal modeller verecektir. Bu çalışmada atmosferik etkiler ve düzeltme metodları, NREL 5MW rüzgar türbini güç eğrisi için incelenmiş ve düzeltilmiş güç eğrisinin önemi tartışılmıştır.
Atmosfer Durumuna ve Yapısal Yorgunluğa Bağlı Güç Eğrisi Güncellemesi
Thesis (Master)--Izmir Institute of Technology, Energy Engineering, Izmir, 2020
Includes bibliographical references (leaves: 71-74)
Text in English; Abstract: Turkish and English
Keywords: Wind turbines; Wind energy; Power curve uptade